2019
DOI: 10.1080/21556660.2018.1563549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of frailty in older people in Veneto (Italy)*

Abstract: Context: Both frailty and multimorbidity are strong predictors of clinical endpoints for older people. In Italy, the interventions targeting chronicity are mainly based on the treatment of diseases: sufficient epidemiological literature is available about these strategies. Less is known about the territorial distribution of the frailty status.Aims: To estimate the prevalence of frailty in older people (65+) and to evaluate the relationship between frailty and multimorbidity.Methods and material: A group of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Secondary objectives were to compare the prevalence of frailty and multimorbidity in Veneto and Sicily. A third objective was to confirm the relationship between frailty and multimorbidity found in our previous research 17 .…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…Secondary objectives were to compare the prevalence of frailty and multimorbidity in Veneto and Sicily. A third objective was to confirm the relationship between frailty and multimorbidity found in our previous research 17 .…”
Section: Introductionmentioning
confidence: 70%
“…That research shows that almost one in five elderly in Veneto is affected by frailty, the raw prevalence being 23.18% (21.53–24.91%). In that experience, to be a female acted as a strong and independent risk factor, while age was shown to be a confounder in regards to the multimorbidity: only in elderly individuals aged below 85 year was a significant multimorbidity shown to be an independent predictor of frailty 17 .…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Also, it was found that the frailty scores of women were higher, but was not significantly correlated with the quality of life (Table 1). Previous studies suggest that frailty is more common in females than in males, however, the reason for this difference has not been elucidated, and female sex was included among the criteria for successful description of frailty (30,31). These results have indicated that the necessity of determining frailty in female elderly individuals and planning the care by considering risk factors is important.…”
Section: Discussionmentioning
confidence: 97%